Coronavirus (Covid-19) Cases in Nigeria and Global Crude Oil Prices: An Empirical Investigation between 2020 and 2022 - Daramola, Imoleayo Oritse-Tsemaye; Ogunwole, Cecilia Oluwakemi; Olasupo, Sunday Festus; Ajagbe, Surajdeen Tunde; Aderemi, Timothy Ayomitunde (Acta Universitatis Danubius. Œconomica, 2022)
Before the advent of the Russia-Ukraine war, Nigeria has been consistently experiencing short falls in meeting the OPEC quotas in the international market for crude oil. As one of the major players in this market, the persistent short falls could orchestrate price dynamics in the international oil market. Meanwhile, continuous rise in Covid-19 cases in 2020 in Nigeria led to the closure of the economic activities in the country, of which could spell doom for both the local and the global aggregate demand and supply of crude oil. Against this backdrop this study utilized the susceptible-infected-recovered (SIR) model to research the influence of Covid-19 cases in Nigeria on global crude oil prices, utilizing information from the relevant sources from the period of 1st March, 2020 to 30th June, 2022. Consequently, this study's conclusions include the following; the confirmed cases and the death cases of Covid-19 in Nigeria had positively induced the global crude oil prices, though not in a significant way. Whereas, the Covid-19 recovery cases in Nigeria had negatively and significantly induced global crude oil prices. However, none of the variables is causally related to one another. From these findings, it is strategic to enunciate that any time the policymakers in OPEC wish to ensure stability in the prices of crude oil in the international market, the Nigerian government in particular and other crude oil exporting countries should take a pragmatic step in curbing the emergence of new waves of Covid-19 cases in their countries.